Mortality from adverse drug reaction-related hospitalizations in south-west Ethiopia: A cross-sectional study - Angamo, M.; Chalmers, Leanne; Curtain, C.; Yilma, D.; Bereznicki, L. (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 John Wiley & Sons Ltd. What is known and objective: Adverse drug reactions (ADRs) are an important cause of mortality during medical care. To our knowledge, no Ethiopian studies have reported on mortality due to ADRs in patients presenting to hospital from the community setting. The aim of this study was to determine the mortality rate attributable to ADRs in patients presenting to hospital, identify drugs implicated in the ADR-related deaths and identify factors contributing to ADR-related mortality at Jimma University Specialised Hospital (JUSH), south-west Ethiopia Methods: This cross-sectional study included 1001 patients aged =18 years consecutively admitted to medical wards from May 2015 to August 2016. ADR-related mortality was determined through detailed review of medical records, laboratory tests and patient interviews followed by causality assessment by the Naranjo algorithm and expert consensus. Results: Of 1001 patients, 15, 1.5% (95% confidence interval [CI]: 0.80%-2.30%) died with an ADR. The primary suspected causes of death were drug-induced hepatotoxicity (7, 43.8%) followed by acute kidney injury (4, 25.0%). Isoniazid (6, 33.3%), pyrazinamide (3, 16.7%), efavirenz (2, 11.1%) and tenofovir (2, 11.1%) were commonly implicated drugs. The majority of ADRs (14, 93.8%) were preventable. Unadjusted bivariate comparisons suggested patients who died with ADRs were more likely to have pre-existing liver disease (40.0% vs 7.0%; 95% confidence interval [CI]: 8.1%-57.8%), a history of ADRs (40% vs 1.4%; 95% CI: 13.8%-63.4%), a lower mean (±SD) body mass index (BMI, 17.6 ± 2.1 vs 20.0 ± 2.9 kg/m2; 95% CI = 0.9-3.9), exposure to antitubercular (46.7% vs 18.9%; 95% CI: 2.3%-53.1%) and antiretroviral (40.0% vs 7.7%; 95% CI: 7.5%-57.2%) therapies, and a higher mean number of medications (7.1 ± 3.3 vs 3.8 ± 2.1; 95% CI: 2.2-4.4) and Charlson Comorbidity Index (3.9 ± 2.9 vs 1.6 ± 1.8; 95% CI: 1.4-3.2) than surviving patients without ADRs. What is new and conclusion: Fatal ADRs were common in patients presenting to hospital. The drugs implicated were mostly antitubercular and antiretroviral therapies, reflecting the high burden of HIV and tuberculosis in the study population. ADR-related deaths were significantly associated with poor nutritional status. The majority of ADR-related deaths were preventable, highlighting the need to develop a multidisciplinary approach to closely monitor patients who are prescribed antitubercular and antiretroviral therapies, particularly in patients with hepatic disease, a history of ADRs, who are malnourished and who are exposed to multiple medications.